Ubiquitous and pervasive computing : concepts, methodologies, tools, and applications - Symonds, Judith, 1972- (Information Science Reference, 2010)
"This publication covers the latest innovative research findings involved with the incorporation of technologies into everyday aspects of life"--Provided by publisher.